Individual Character: A Perspective - Opatha, H.H.D.N.P. (Department of Human Resource Management Faculty of Management Studies and Commerce University of Sri Jayewardenepura, 2007)
Seemingly Western literature and Eastern literature of Human Resource Management (HRM) reveal a gap in the theoretical knowledge as well as the empirical knowledge in respect of Individual Character (IC) and human resource development through character building. Studies will have to be carried out in order to develop a pragmatic framework of describing character and explaining its dynamics; a logical model of explaining the relationship between character and HRM; and a pragmatic framework of character development at the micro (organizational) level. Though there are several research questions which need to be answered systematically and scientifically, the objective of this research paper was to explore what IC means, whether IC differs from the concept of so called personality and why IC is important, specially in current Sri Lankan context. Ostensibly, the approach of the paper was reflective and descriptive. IC was defined as the aggregate of all of the relatively persistent moral qualities a person has that combines to form his/her real nature. It is the degree to which the person possesses the virtues and do not possess the vices. Virtues are to be nurtured within the individual while vices are to be removed from the individual for the purpose of developing IC. It was asserted that IC was not the so called personality and it differed significantly from personality in several ways. It was substantiated by literature that IC is of utmost importance for individual development, organizational development and nation development as well.
Keywords: Individual Character, Morality, Personality, Values, Vices, Virtues